3D printing MOFs‐based fiber electrodes: A novel platform as electrochemical sensors for heavy metal ions. Issue 22 (21st September 2022) - Li, Yanping; Wan, Yating; Wang, Yafei; Zhang, Yan
Abstract: Pb 2+ probes play an important part in environments and human health. We developed a new free‐standing electrochemical probe by 3D printing UiO‐66‐NH2 with @rGO. This free‐standing fiber electrochemical sensor exhibited good structural stability and Pb 2+ sensing performance with enhanced conductivity. This MOFs‐based hybrid probe showed an excellent sensing sensitivity for Pb 2+ with a very low detection limit of 0.041 μM, significantly lower than the standard for Pb 2+ in drinking water as a result of the porous structure of UiO‐66‐NH2 and the good conductivity of rGO. This study highlighted a simple strategy for MOFs‐based hybrid sensor formation and accelerated the MOFs‐based materials for Pb 2+ electrochemical detection in future practical applications. Abstract :